2007
DOI: 10.1016/j.labeco.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of job satisfaction on job search: Not just whether, but also where

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 31 publications
0
34
0
1
Order By: Relevance
“…Flanagan et al 1974;Freeman 1978;Clark et al 1998;Ward and Sloane 2000;Clark 2001;Kristensen and Westergård-Nielsen 2004;Delfgaauw 2007;Lévy-Garboua et al 2007). These studies discover that dissatisfied workers are more likely to quit their current matches.…”
mentioning
confidence: 99%
“…Flanagan et al 1974;Freeman 1978;Clark et al 1998;Ward and Sloane 2000;Clark 2001;Kristensen and Westergård-Nielsen 2004;Delfgaauw 2007;Lévy-Garboua et al 2007). These studies discover that dissatisfied workers are more likely to quit their current matches.…”
mentioning
confidence: 99%
“…Based on data retrieved from cross-national surveys Souza-Poza and Henneberger [4] found that job satisfaction has one of the strongest influence on intentions to quit. Using survey data of public sector employees in the Netherlands, Delfgaauw [16] shows that workers' satisfaction with various job domains not only affects whether but also where workers search for another job. The author argues that workers try to leave their current employer when they are uncomfortable with an organisation-specific job domain, like management, but when they are dissatisfied with a job domains which may have an industry-specific component, such as job duties, they want to leave their industry.…”
Section: Does Wage Cut and A Wage Increase Have A Significant Effect mentioning
confidence: 99%
“…The study also disclosed some evidence supporting the adaptive impact of anxiety and individual properties as its moderators. Delfgaauw (2007) investigated that workers' satisfaction with various job domains not only affects whether but also where workers look for another job based on a survey data of public sector employees in the Netherlands. They explained that workers attempt to quit their jobs when they feel uncomfortable with an organization-specific job domain, e.g.…”
Section: Introductionmentioning
confidence: 99%